Penataan Kelembagaan Keluarga Berencana di Provinsi Kepulauan Riau - lestari, ayu fuji (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2017)
The purpose of this study is to formulate a policy alternative institutional arrangement of familyplanning effective and efficient. The method used is descriptive qualitative research that describes asocial phenomenon without comparison and answer hypothesis. In this study, researchers used thetheory of William N Dunn with the problem formulation process analysis and policyrecommendations, and informants in this research were as many as seven people. Data analysistechnique in this research is to use three grooves activities going on simultaneously: data reduction,data presentation and conclusion. The results of this study is the lack of commitment of the centralgovernment and local governments in the province of Riau Islands KB institutional arrangement inTanjungpinang so far has not been established BKKBD in regencies / cities in Riau Islands Province.And the alternative is on offer is immediate establishment of BKKBD in Tanjungpinang and makeFamily Planning Field Officers made in the Civil Service.